Dynamic transition to a sustainable waterfront development in Penang, Malaysia - Tan, Daniel Ying Shin; Woo, Suk Wah; Wong, Yee Chin (International Journal of Sustainable Development & World Policy, 2024)
The interactions between human with land and water in realizing economic dynamism and sustainability with vast diversity human usage and needs is a great challenge that often with the resultant of rising tensions among stakeholders and the users. While the right to development is an absolute human right, along the development pathway should at least preserve or sustain the ecological systems for the future generations while maintaining the socio-economy balance. This paper firmly positions its study on Penang and applying the mixed mode research methods to reveal the underlaying elements to examine the sustainable waterfront development goals that will benefit the stakeholders and users of Penang. These underlaying elements plays a pivotal solution in addressing the rapid development with land and water. It emphasizes the proactive measures that can be undertaken to restrain economic, social and ecological systems risks, cultivating an improved and congruent environment for both the stakeholders and users of Penang. The mixed mode method used in this paper was the quantitative approach that collects data from questionnaires surveys and qualitative approach covers interviews where the analysis point of interface converged the results producing a constructive good health, quality education and deserving a quality living place as a sustainable inference to address the land and water mixed application challenges in Penang.